OCEAN OBSERVATION ON SST VARIABILITY AND SUBSURFACE SEA WATER TEMPERATURE OF THE NORTH PAPUA THE FATE OF EL_NINO 1997 & 2007 AND LA NINA 2002 : FIELD MEASUREMENT AND TRITON BUOY DATA - Agus Hartoko (JOURNAL OF COASTAL DEVELOPMENT, 2009)
The increasing need to introduce and emphasis the analysis of SST and its sub-surface layers of deepwater temperature (both horizontal and vertical) profile to analyze some oceanographic phenomenasuch as up-welling process and its relationship to its seasonal variability and spatial distribution wasinevitable. Especially to avoid the misleading interpretation of using only sea surface temperature datafor deep water fish biomass distribution analysis, etc. Field SST data of July – August 1997 wasmeasured by CTD (Conductivity-Temperature-Depth) sensors on board of RV. BARUNA JAYA IV withaccuracy of 0.01 °C. Field SST data of 2002 and 2007 was derived from TRITON Buoy data base withpermission of Jamstec-Japan. All field and TRITON buoy SST data were processed into a spatial SSTlayer using Kriging method with Er_Mapper (Licensed user) software, and overlaid on the bathymetriclayer. Average daily SST east monsoon 1997 (El Nino event) was 28.46°C, where as presumably LaNina event 2002 : the average daily SST was 29.75°C and for 2007 was : 29.83°C indicates a higher SST than both 1997 and 2002. Average daily SST of west monsoon 2007 was 29.69°C. Daily SST of 2007 east monsoon was about 0.08 - 0.5°C higher than the same season of 2002 (TRITON Buoy data).The paper analyze and revealed the fate / occurrence of up welling zone in adjacent of Halmahera islands as well as the Hot Event (HE) phenomena through the analysis based on multi-layer and subsurface horizontal of both horizontal and vertical temperature of the field measurement 1997 and 2002 and 2007 TRITON data. Spatial multi-depth-layer approach had been developed in the paper is important for the analysis of deep water large pelagic fishery such as tuna fishery and its spatial distribution pattern.